1998
DOI: 10.1038/2919
|View full text |Cite
|
Sign up to set email alerts
|

Structure of α-lytic protease complexed with its pro region

Abstract: While the majority of proteins fold rapidly and spontaneously to their native states, the extracellular bacterial protease alpha-lytic protease (alphaLP) has a t(1/2) for folding of approximately 2,000 years, corresponding to a folding barrier of 30 kcal mol(-1). AlphaLP is synthesized as a pro-enzyme where its pro region (Pro) acts as a foldase to stabilize the transition state for the folding reaction. Pro also functions as a potent folding catalyst when supplied as a separate polypeptide chain, accelerating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
88
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 32 publications
2
88
0
Order By: Relevance
“…2B). The alpha-lytic protease also has a C-shape propeptide (23), but the interfaces between the propeptide and the catalytic domain for the two proteases are different. The concave surfaces of both the FTP and PepSY domains are lined by four antiparallel β-strands, whereas their convex centers consist of two α-helices packed against the above β-sheets to form the hydrophobic core.…”
Section: Resultsmentioning
confidence: 99%
“…2B). The alpha-lytic protease also has a C-shape propeptide (23), but the interfaces between the propeptide and the catalytic domain for the two proteases are different. The concave surfaces of both the FTP and PepSY domains are lined by four antiparallel β-strands, whereas their convex centers consist of two α-helices packed against the above β-sheets to form the hydrophobic core.…”
Section: Resultsmentioning
confidence: 99%
“…After the cleavage, the N terminus dissociates out of the active site and then forms a final conformation identical to the crystal structure. The idea was derived from the crystal structure of the precursor of the ␣-lytic protease, a serine protease, which underwent autocatalytic cleavage during maturation (37). This model implies that the Arg8 residue is important for the 3B/3C cleavage, but is not necessary for cleavage at the other junctions.…”
Section: Vol 76 2002 Active-site Residues In Chiba Virus 3c-like Prmentioning
confidence: 99%
“…The structure of αLP bound by its pro region showed that the pro region is a two-domain C-shaped protein that binds to and surrounds the αLP C-terminal domain (27). Based on these results, it was hypothesized that much of the folding defect of αLP would be localized to the C-terminal domain.…”
mentioning
confidence: 99%